Development An Android Based Pemeriksaan 5 Menit (P5M) Information System - Kristanto, Candra Bagus; Goffar, Eko Abdul; Rascalia, Radix (Institut Teknologi Dirgantara Adisutjipto, 2019)
P5M is a readiness inspection activity such as the attributes and attendance of students before practicing. Students whose attributes are incomplete will be recorded in P5M sheet. Each attribute has a violation point or hour minus. P5M data, will recapitulate the number of hours minus. Constraints that occur in the Astra Manufacturing Polytechnic, namely the filling process of P5M sheets is still manual. This causes the time required to recapitulate minus hours to be long, which is on average 5 minutes. This causes the process of renewing the number of hours minus students and the process of paying hours minus being hampered. To overcome this, an Android-based P5M information system was made. This information system was developed using the Extreme Programming methodology and the MySQL database. With the P5M information system, it can eliminate the process of recapitulation of minus hours and reduce paper usage.